EDUKASI PENYAKIT HIPERTENSI WARGA DUKUH GEBANG RT 04/RW 09 DESA GIRISUKO KECAMATAN PANGGANG KABUPATEN GUNUNGKIDUL - Muchamad Rifai; Diah Safitri (LPPM ITB AAS Indonesia Surakarta, 2022)
Hypertension is a disease defined as a persistent increase in blood pressure. From the results of Community Diagnosis, hypertension is the main problem in RT 04 Gebang Village because there are still many people who refer to this disease. The purpose of this activity is to explore the main problems faced by the community based on existing facts and to take strategies and follow-up plans to resolve these problems. At the time of identifying the problem using Indepth Interview or in-depth interviews conducted door to door to the community at the community home of RT 4 Gebang Village. From the interviews that have been conducted, there are several indicators in it, namely regarding non-communicable diseases, infectious diseases, occupational safety and health, environmental health, mental disorders, traditional health services and covid-19. The method used in determining the priority of the problem is the USG (Urgency, Seriousness and Growth) method. Based on the results of the ultrasound assessment in determining the priority of problems, from 7 non-communicable disease problems, they were reduced to one biggest problem, namely hypertension.